Novel Coil Winding Method to Realize Pot Heated Evenly - Mao-Yan Wang; Hai-Long Li; Meng Zhang; Zhi-Tao Xu; Cui-Lin Zhong; Jun Xu (电子科技学刊, 2015)
To solve the problem about the inhomogeneous thermal effect of pot heated by coils along the circumference, a novel coil winding method is proposed and compared with the general winding method in the paper. First, based on the Biot-Savart law and Ampere’s rule, the magnetic induction generated by a straight current carrying conductor and a current loop is discussed, respectively. Then the novel coil winding method is developed by adjusting the location of inhomogeneous joints. The joints are periodically scattered along the circumferential direction and symmetrically designed around the central axis. Numerical results show that the quite non-uniform temperature in the base of pot at the circular direction is effectively improved by using the proposed winding method. The potential danger produced by high temperature at some region of coils plate is minimized. It is energy-efficient and safe for residential appliances.